High prevalence of low bone mineral density in middle-aged adults in Shanghai: a cross-sectional study - Qian Chen; Dan Liu; Xuefei Li; Fangfang Li; Suxia Guo; Shiyun Wang; Weina Yuan; Pinghua Chen; Pan Li; Fangyu Li; Changwei Zhao; Wen Min; et al. (BMC Musculoskeletal Disorders)
Abstract Purpose To assess bone mineral density (BMD) in middle-aged individuals in Shanghai, in order to improve awareness of osteopenia and osteoporosis screening. Methods The clinical data of 1107 permanent residents of Shanghai aged 40–60 years were collected using a random cluster sampling method. Osteoporosis questionnaire survey and BMD test were conducted. Mann-Whitney U and Chi-square test were used to compare sex, age and body mass index at different stages of bone mass, and Pearson test was used to conduct correlation analysis. Logistic regression was used to analyze the influencing factors. Results The detection rates of osteopenia and osteoporosis were 59% and 12.5% respectively, and bone mineral density was correlated with sex, age, and body mass index (P < 0.05). Conclusion The incidence of low bone mass is high in the assessed population, screening for low bone mass should be actively carried out to improve public awareness. It is also good for public health management. Registered clinical trial The trial was approved by Chinese Clinical Trial Registry on February 11, 2021(ChiCTR2100043369).